Occurrence, human health risks, and public awareness level of pharmaceuticals in tap water from Putrajaya (Malaysia) - Sarva Mangala, Praveena; Maizatul Zahirah, Mohd Rashid; Fauzan Adzima, Mohd Nasir; Wee, Sze Yee; Ahmad Zaharin, Aris (Springer, 2020)
Pharmaceutical residue pollution remains as an underexplored issue, especially in Asian countries. Along with that line, the purpose of this study was to investigate the occurrence of pharmaceutical residues in tap water and its associated potential health risks, involving a total of 80 Putrajaya residents. Besides, this study also aimed to evaluate public awareness (knowledge, attitude, and practice) levels with regards to pharmaceutical handling. The highest pharmaceutical residue occurrence was cafeine (0.38 ng/L) while the lowest was diclofenac (0.14 ng/L). These pharmaceutical residue occurrences in tap water were linked with rapid urbanization and industrialization in river water, poor removal efciencies in wastewater and drinking water treatment plants as well as improper pharmaceutical waste handling and disposal from the general public. The potential health risks (RQT) indicated residents in Putrajaya with ages between 61 and 75 were exposed to the highest health risks caused by the pharmaceutical residues in tap water. In general, low public awareness (knowledge, attitude, and practice) levels were identifed with only 44.5% of Putrajaya population having good knowledge, 27.5% having good attitude and 1.6% having good practice related to pharmaceutical handling and its efect to tap water quality. Findings of this study refected the importance of public awareness program to educate the general public on proper unused/expired handling and disposal to minimize pharmaceutical pollution.